Analisis Penggunaan Mazmur Hikmat Dalam Ibadah Israel Kuno Dan Relevansinya Terhadap Liturgi Gereja Toraja - Heni Maria; Wina Paembonan; Yudita Tiara Sambira; Erick Bine Sampe (Jurnal Teologi Praktika, 2022)
This study aims to to analyze the use of psalms wisdom in worship of the ancient israelites and its relevance terdap toraja church liturgy .As we know and i will sing praise certificate is a hallmark of the liturgy of the early church singing psalms were of one piece with attention psalm especially in important in the church toraja psalm reciprocating can be read , namely reading from a written note that have parked and into reciprocating as well as to the people of liturgical leader , can also use women and men .And to find out more writer wearing a method of exposition and also by increasing the qualitative research was conducted by the use of books and research diperpustakaan by conducting field a number of interviews .In the book of psalms it has meaning namely giving guidance to get a feeling about the same as in giving guidance bible passages to faith and our actions. The functions and benefits and meaning of reality is for the congregation of the lord in ancient times even now used by the hebrews in church at the temple and jews today use it in rumah-rumah sembayang mereka.orang christian anciently will sing it can be seen in colossians 3: 16 , james 5: 13 and hitherto has always worn all by the lord , which is priceless to the service, comfort , grace or unmerited favor , and steadiness with joy , specifically in the toraja of worship a church.